PERLINDUNGAN HUKUM ATAS HAK KENYAMANAN KONSUMEN SEBAGAI PENGGUNA JASA TRANPORTASI KERETA API COMMUTER LINE KHUSUS WANITA - Gabriella Evanggelista; Siti Nurbaiti (Fakultas Hukum Universitas Tarumanagara, 2018)
Nowadays, a convenient transportation needs are increasingly needed by the public including transportation for women’s Commuter Line train. However, in practice there was still inconvenience in using the Woman’s Exclusive commuter line train transportation. How is the legal protection of customer’s right to comfort as a user of the Women’s Exclusive commuter line Transportation service trains is a problem discussed. The research method used is a descriptive normative research method which is based on secondary data and primary data as supporting data which is analyzed qualitatively. The results of the study illustrate that PT KCI has not provide legal protection for female special line commuter train service users as stipulated in Article 3 Railway Law No. 23 of 2007 and Article 4 Paragraph (1) Customer Protection Law No. 8 of 1999 , the inconvenience caused by the Women’s Special commuter line train is always full tight and has caused one of the train passangers to faint.